Reconstruction of walking motion without flight phase by using computer simulation on the world elite 20km race walkers during official races - Hoga-Miura, K.; Hirokawa, R.; Sugita, M. (Slovak Journal of Sport Science, 2017)
BACKGROUNDS: Article 230 of competition rules of athletics specify that race walking should be judged by human eye of the race walking judges, but during races even highly skilled race walking judges may sometimes not recognise a brief flight time as "Loss of Contact" time. Electric or visual devices for race walking judge will be innovated and applied to the race walking event. Then, the training methods to avoid flight phase should be established. AIMS: The purpose of this study is to obtain basic findings of the walking motion without flight phase. From three- dimensional coordinate data of athlete in the real official competition, virtual three-dimensional coordinate will be calculated and the joint kinetics will be obtained by using inversed dynamics. METHODS: Two kinds of computer simulation were conducted on the three-dimensional whole body coordinates data of sixteen world elite male walkers collected in the elite official race (Olympic games held in 2004 and World championships in Athletics held in 2005) for Men's 20kmW. In most of elite race walkers, their recovery phase time was larger than the support phase time. One simulation directed to diminish the flight phase by setting the recovery phase same as the support phase of contralateral leg. Another simulation directed to diminish the flight phase by setting the start of the support phase as the start of the recovery phase of contralateral leg. RESULTS and CONCLUSION: In the simulation, which directed to reduce the recovery phase time, the walking speed was reduced because of the short step length. However, the larger joint torque at hip and knee exerted rather than the real data. In the simulation, which directed to expand the support phase time, the walking speed was same as the real data. Although the large joint torque at hip and knee exerted rather than the real data, the hip abductors' torque which was large in the walkers without flight phase in the official race and experiment was reduced in the simulated data. From these results, it is important large flexors' and extensors' torque at knee and hip were important to walk without flight phase. However, the simulation in the frontal plane should be conducted in the future.